2013
DOI: 10.1186/1758-2946-5-47
|View full text |Cite
|
Sign up to set email alerts
|

Complementary PLS and KNN algorithms for improved 3D-QSDAR consensus modeling of AhR binding

Abstract: Multiple validation techniques (Y-scrambling, complete training/test set randomization, determination of the dependence of R2test on the number of randomization cycles, etc.) aimed to improve the reliability of the modeling process were utilized and their effect on the statistical parameters of the models was evaluated. A consensus partial least squares (PLS)-similarity based k-nearest neighbors (KNN) model utilizing 3D-SDAR (three dimensional spectral data-activity relationship) fingerprint descriptors for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Supplemental Data, Table S1 (see also Figure ) indicates that the PLS and KNN algorithms achieve their best predictive performance at a different granularity of the 3D‐SDAR space. Similar behavior has been observed previously and was attributed in part to the effect of 13 C simulation error and the way PLS and KNN process input data. Although the parametric space surfaces shown in Figure for both types of model have multiple local maxima, in general PLS is more effective at bin sizes (0.5 Å × 14 ppm × 14 ppm, average R 2 test = 0.743) larger than those for KNN (0.5 Å × 8 ppm × 8 ppm, average R 2 test = 0.764).…”
Section: Resultssupporting
confidence: 85%
“…Supplemental Data, Table S1 (see also Figure ) indicates that the PLS and KNN algorithms achieve their best predictive performance at a different granularity of the 3D‐SDAR space. Similar behavior has been observed previously and was attributed in part to the effect of 13 C simulation error and the way PLS and KNN process input data. Although the parametric space surfaces shown in Figure for both types of model have multiple local maxima, in general PLS is more effective at bin sizes (0.5 Å × 14 ppm × 14 ppm, average R 2 test = 0.743) larger than those for KNN (0.5 Å × 8 ppm × 8 ppm, average R 2 test = 0.764).…”
Section: Resultssupporting
confidence: 85%
“…As described in the Modeling approach section, 3D-SDAR performs multiple randomizations on the modeling set and reports averages of the aggregated predicted values [33,39]. Because it is not based on topology or structural fragments, 3D-SDAR can determine a set of substructural units, as well as the distances between them that are related to the compounds' biological activity.…”
Section: Structural Patterns Associated With Estrogenicitymentioning
confidence: 99%
“…This generalized structural pattern is commonly referred to as either a pharmacophore or toxicophore. As described in the Modeling approach section, 3D-SDAR performs multiple randomizations on the modeling set and reports averages of the aggregated predicted values [33,39]. Simultaneously, the PLS algorithm records the first N (N is a user-defined parameter) heavily weighted bins for each latent variable.…”
Section: Structural Patterns Associated With Estrogenicitymentioning
confidence: 99%
“…In this project, information about the presence of atoms other than carbon was not explicitly included. We have found in several of our previous SDAR modeling projects that the high sensitivity of 13 C δs to their environment is often sufficient for useful reflection of chemical structure in the vicinity, including the presence of nearby heteroatoms [ 1 , 3 , 4 ]. A tessellation of the 3D-SDAR space into regular grids (“binning”) is further used to convert the information contained in a fingerprint into a set of 3D-SDAR descriptors.…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier studies indicated that 3D-QSDAR models based on lowest energy conformations perform well [ 1 , 3 , 4 ]. However, we hypothesized that use of substrates internally aligned with respect to molecular template molecules rather than energy-minimized conformations might prove beneficial.…”
Section: Introductionmentioning
confidence: 99%